Overall strategic analysis of clean energy technology in the European Union - Georgakaki, Aliki,Letout, Simon,Kuokkanen, Anna,Mountraki, Aikaterini,Ince, Ela,Shtjefni, Drilona,Taylor, Nigel,Schmitz, A.,Vazquez Dias, A.,Christou, M.,Pennington, D.,Mathieux, F. (Publications Office of the European Union, 2022)
This report is part of an annual series from the Clean Energy Technology Observatory that address the status of technology development and trends, value chains and markets in the European Union and internationally. The present report aims to provide an overall integrated analysis of the clean energy technology and system integration. It addresses two main aspects: a) data on the overall competitiveness of the EU clean energy sector and b) strategic analysis of critical value chains and sustainability.
10.2760/12921
Keywords: Graue Literatur; Amtliche Publikation; Saubere Energie; Erneuerbare Energie; Energietechnik; Internationaler Wettbewerb; Forschung; Humankapital; Nachhaltigkeit; Wertschöpfung; EU-Staaten; clean technology; technological change; energy market; research and development; innovation; energy research; value chain; energy technology; competitiveness; price of energy; civic engagement; research expenditure (EU); intellectual capital; added value; energy production; sustainable development; report